Urgensi Surat Berharga Obligasi Dalam Pemenuhan Hak Dan Kewajiban Perusahaan dan Investor Dalam Pasar Modal - Linda Uril Khofifah; Ainun Najib; Sumriyah Sumriyah (Jurnal Relasi Publik, 2023)
The company is an organized institution with the aim of obtaining profits in the development of companies in the capital market and providing opportunities for the public to invest in the short, medium and long term, while it is easier for companies to obtain funds from the public investors (investors) by issuing securities both equity or debt. The purpose of this research is to find out how bonds are regulated in the Indonesian capital market from legal protection and corporate responsibility that defaults on bond investors. This study uses a normative legal research method that focuses on the study of legal perspectives and/or perspectives that explain a set of legal principles, legal norms, and legal regulations both formally and materially. The approach used in research is a conceptual approach (Conceptual Approach) where by examining through legislation and theories. Based on the research results, it is known that bond investors protect capital from the risk of company default, namely periodic reports and transparency of information, as well as guarantees (collateral) included in the issuance of bonds and the existence of sinking funds (reserve funds). Preventive legal protection for investors after a default occurs, the company continues to pay bond principal and interest (coupons) to investors in accordance with the bond agreement agreement. Companies can also be subject to civil witness administrative sanctions and even criminal sanctions.